“Infecting the mind”: Burnout in frontline healthcare professionals of COVID-19 in Brazil (Research, Society and Development, 2022)
With the pandemic caused by the new coronavirus, the world is experiencing, from the perspective of Public Health, a serious global health crisis, having to face an intense and complex challenge. Health professionals experience a period of greater pressure, with the potential to adversely affect their physical and mental health, leading to the emergence of disorders related to stress and anxiety. Systematize scientific evidence related to Burnout Syndrome in health professionals who work on the front line of COVID-19 care in Brazil. Papers indexed in PubMED® and the Virtual Health Library (VHL) were analyzed, with 06 studies being part of this review, which met the selection criteria. Consistent reports of stress, anxiety, and symptoms of depression in healthcare workers were identified. The studies show similarities with regard to the existence of fatigue, exhaustion and exhaustion, associated with greater psychic suffering, compatible with Burnout Syndrome, as a result of care on the front line of COVID-19. In the face of evidence, Burnout Syndrome is a reality in health professionals at the forefront of the battle in the pandemic. Research on strategies to improve the well-being of these professionals is suggested.